2020
DOI: 10.7554/elife.52358
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila TRIM32 cooperates with glycolytic enzymes to promote cell growth

Abstract: Cell growth and/or proliferation may require the reprogramming of metabolic pathways, whereby a switch from oxidative to glycolytic metabolism diverts glycolytic intermediates towards anabolic pathways. Herein, we identify a novel role for TRIM32 in the maintenance of glycolytic flux mediated by biochemical interactions with the glycolytic enzymes Aldolase and Phosphoglycerate mutase. Loss of Drosophila TRIM32, encoded by thin (tn), shows reduced levels of glycolytic intermediates and amino acids. This altered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 80 publications
10
29
0
Order By: Relevance
“…In control larvae, larval locomotion velocity increases as the larvae progress through the instars [ Figure 5 I, ( Balakrishnan et al., 2020 )]. This increase in locomotion velocity throughout larval stages is consistent with an increase in muscle size that occurs during the instars ( Balakrishnan et al., 2020 , Demontis and Perrimon, 2009 , Bawa et al., 2020 ). Mutations in genes affecting larval locomotion thus far have predominantly decreased locomotion, with very few mutations identified that increase locomotion of the larva ( Camuglia et al., 2018 ).…”
Section: Expected Outcomessupporting
confidence: 78%
“…In control larvae, larval locomotion velocity increases as the larvae progress through the instars [ Figure 5 I, ( Balakrishnan et al., 2020 )]. This increase in locomotion velocity throughout larval stages is consistent with an increase in muscle size that occurs during the instars ( Balakrishnan et al., 2020 , Demontis and Perrimon, 2009 , Bawa et al., 2020 ). Mutations in genes affecting larval locomotion thus far have predominantly decreased locomotion, with very few mutations identified that increase locomotion of the larva ( Camuglia et al., 2018 ).…”
Section: Expected Outcomessupporting
confidence: 78%
“…Regarding the C-terminal NHL repeats, no structural data is available for either protein, but the high sequence similarity between TRIM32 and malin would suggest that the NHL domain presents a similar three-dimensional structure. The crystal structure of the NHL domain of the TRIM32 Drosophila orthologue, thin , was recently solved and shown to fold in the typical beta-barrel shape (PDB 6D69; 6XG7) [ 31 , 32 ]. Using the Swiss-Model homology modeling software ( , accessed on 1 January 2021) and the crystal structure of the C-terminal domain of Danio rerio TRIM71, another NHL-containing TRIM (PDB 6FPT), we modeled the C-terminal domain of both malin and TRIM32 ( Figure 3 C).…”
Section: Structural Data and Biochemical Function Of Trim32 And Malinmentioning
confidence: 99%
“…The role of malin, in complex with laforin, in glycogen catabolism has been extensively described above. Interestingly, in the D. melanogaster model, the TRIM32 orthologue thin was recently shown to be implicated in glucose metabolism through the positive regulation of glycolytic enzymes aldolase and phosphoglycerate mutase [ 31 ]. In addition, TRIM32 silencing in normal muscles increases PI3K-AKT-FOXO signaling and enhances glucose uptake, thus inducing fiber growth [ 98 ].…”
Section: Malin and Trim32 Common Pathways?mentioning
confidence: 99%
See 1 more Smart Citation
“…2 C.2). A glycolysis-dependent amplification loop may exist in Pvr tumors too, as tripartite motif-containing protein 32 (TRIM32; encoded by thin ), an E3 ubiquitin ligase that maintains glycolytic flux, is required for LDH transcription in tumors ( Bawa et al, 2020 ). Nonetheless, how TRIM32 controls LDH at the transcriptional level in Pvr tumors warrants further investigation.…”
Section: The Warburg Effectmentioning
confidence: 99%